Laser based 100 GeV electron acceleration scheme for muon production - J. D. Ludwig; S. C. Wilks; A. J. Kemp; G. J. Williams; N. Lemos; E. Rockafellow; B. Miao; J. E. Shrock; H. M. Milchberg; J.-L. Vay; A. Huebl; R. Lehe; et al. (Scientific Reports)
Abstract High energy muons, due to their unique ability to penetrate deeply into matter, can enable radiography of structures that cannot be probed by other forms of radiation. Current terrestrial sources of muons require conventional GeV-TeV particle accelerators which are hundreds to thousands of meters in size. Laser wakefield acceleration (LWFA) can achieve acceleration gradients of two-to-three orders of magnitude greater than conventional accelerators, thus shrinking the accelerator to a number of meters. We propose a concept for a compact muon source based on the first self-consistent PIC simulations of an all optical LWFA that uses a guiding channel to achieve electron energies of 100 GeV in a distance of 6 m with a driving laser energy of 300 J in a single stage. From the resulting electron energy spectrum we estimate muon production for this source. We show that this accelerator, coupled with high average power laser driver technology, provides the basis for a high energy and high flux muon source.